ANALISIS PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT PEGADAIAN CABANG MANDALA KOTA MEDAN - Haris Sanri Alka; Muhammad Fauzan Azmy; Rizky Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of training and compensation on employee performance at PT Pegadaian Mandala Branch, Medan City. The background of this research is based on the importance of human resources as the main asset of a company, where improving employee quality through structured training programs and appropriate compensation is expected to enhance performance. The research method used is a quantitative approach with data collected through questionnaires distributed to employees and analyzed using multiple linear regression. The results show that training has a positive and significant effect on employee performance, meaning that the better the training programs provided, the higher the employees’ competence and work productivity. The results of multiple linear regression analysis show that training has a positive and significant effect on employee performance with a coefficient value of 0.421 and a significance level of 0.000 < 0.05. Compensation also has a positive and significant effect on employee performance with a coefficient value of 0.367 and a significance level of 0.002 < 0.05. Simultaneously, training and compensation significantly affect employee performance, as indicated by an F-value of 28.754 > F-table of 3.23 and an R² value of 0.652, meaning that 65.2% of the variation in employee performance is explained by training and compensation, while the remaining 34.8% is influenced by other factors not examined in this study.